Sallust and the Fall of the Republic : Historiography and Intellectual Life at Rome - Shaw, Edwin (Historiography of Rome and Its Empire, 2022)
This book offers a new interpretation of the Roman historian Sallust, which places him at the centre of the rich intellectual world of late Republican Rome. Drawing on the evidence of Sallust's digressions in particular, and in contrast to previous views of his work as purely moralistic or unsophisticated, it argues that Sallust uses his historiography to advance a coherent set of ideas about the political chaos he saw around him, and to participate in the broader debates which characterised his period. It also offers a new perspective on the argumentative qualities of classical historiography more widely.